Determinants of biogeographical distribution of grasses in grasslands of South America - Streit, Helena; Bergamin, Rodrigo S.; Andrade, Bianca O.; Altesor, Alice; Lezama, Felipe; Perelman, Susana; Müller, Sandra C.; Overbeck, Gerhard E. (Perspectives in plant ecology, evolution and systematics, 2024)
Current distribution of C3 and C4 grasses is often explained by contrasting environmental conditions. Regions where C3 and C4 grasses coexist, as the Southeastern South America grasslands (SESA grasslands), provides an excellent opportunity to investigate the evolutionary imprints of grasses through clade distribution patterns. Here, we aimed to understand how ecological and evolutionary processes affect the phylogenetic diversity of grass communities along 666 sites located in a latitudinal gradient ranging from 26°S to 38°S in SESA grasslands (Argentina, Brazil, and Uruguay). We applied generalized linear models (GLM) to understand the role of the different environmental and historical drivers that shape the proportion of C3 grasses distribution in SESA grasslands. The effect of latitude on phylogenetic beta-diversity patterns among the vegetation surveys was evaluated through principal coordinates of phylogenetic structure. Contribution of C3 species increased southwards (R² = 0.40, P<0.001). C3 species are more likely to occur in colder areas with higher historical temperature stability, reflecting lineages that have specialized and radiated in cold environments (GLM results: R² = 0.37, P<0.01). Climatically stable areas are the coldest, while unstable areas include warmer habitats, which enabled colonization by C4 species. Regarding soil conditions, C3 grasses are more likely to occur in more fertile soils and with low capacity to retain water (GLM results: pseudo-R² = 0.37, P<0.01). We found that phylogeny has an important role as a structuring agent of grass communities across our study region, indicating turnover of grass lineages along the latitudinal gradient. Grass species found at the northern portion of the gradient belong mostly to the clade which contain both C4 and C3 species. At the southern part of the gradient, communities are dominated by grasses belonging to a C3-exclusive clade. The distribution of grass clades across the SESA grasslands is indicative of the environmental gradients found in this region between temperate and tropical zones, describing a climate space where disturbance driven feedbacks play a major role in maintaining open vegetation. Our results contribute to the understanding of ecological and evolutionary drivers of grass distribution in the region that up to now has been poorly described. •Grass clades reflect the environmental shift between temperate and tropical zones.•C3 species dominate in climatic stable areas.•Historical climatic instability enabled colonization by C4 species.